Solve two simple math problems

preview_player
Показать описание
Solve these two math problems.

#shorts

As a thank you for all those who are coming from my videos Puzzlemaster offers Worldwide Free Shipping on orders of $99 and over using the coupon code available here:

Download free solutions for puzzles here

Рекомендации по теме
Комментарии
Автор

Imagine actually arguing about THE MOST basic math you can possibly get

pace_
Автор

It's quit hilarious how many answers people confidently give, despite being so wrong, despite there being only one right answer, and a very clear and easy to follow method to solve these simple equations.

frakis
Автор

I feel like the first one should equal 1, because of PEMDAS. Distributive property involves parenthesis, and thus you do that first.

thechickengod
Автор

It should be 9 and 1, but for some reason, my brain won’t give it a rest

parkermace
Автор

Equation one = 1
6/2(1+2)=
6/2(3)=
6/6=1
Equation two = 1
9 -3/1/3 +1 =
[denominator of a denominator is a numerator so:]
9-3*3+1=
9-9+1=1

Try:
The coefficient of x^4 in (y - 2x)^10 equals 215, 040
Find the value of y without fully expanding.

trevaaalee
Автор

Some of you are brimming with confidence.

You can't go straight to division after adding what's inside the parentheses.

If you do it step by step, it's gonna look like this:
6 ÷ 2 ( 1 + 2 )
6 ÷ [ 2 ( 1 ) + 2 ( 2) ]
6 ÷ [ 2 + 4 ]
6 ÷ [ 6 ] = 1

To make things easier, if you input the original equation into a scientific calculator, you should get 1 as the answer.

rhrdth
Автор

The answers are both 1. Don't forget the rules. Solve for parentheses first; divide and multiply second; and addition and subtraction last. In the simple rules, exponents come first, but aren't used in these two simple equations. 6÷6 = 1. 9-(3*3)+1= 1 = 9-9+1= 1

thetron
Автор

6 / 2 (1+2) =

Amazing that this causes so much confusion. Arithmetic operations of equal precedence are performed left to right (at least in nations like the UK, USA, NZ, Australia and Western Europe. Just like reading English is performed left to right.
The precedence implied in a written arithmetic expression is Brackets (or braces, parentheses) first. Next multiplication and division. Finally addition and subtraction. So evaluating INSIDE the brackets comes first. Once you get to a simple number YOU REMOVE THE BRACKETS.
In the absence of an explicit operator, two adjacent expressions are to be multiplied. In algebra, 2a + b means 2 x a + b.
The missing and implied operator is multiplication.
using these two rules (brackets first, implied multiplication),
6/2(1+2) = 6/2(3) = 6/2x3 = 3x3 = 9.

Perhaps the confusion comes from trigonometric equations like sin(y), where the braces indicate the argument of the sine function, and NOT an implied multiplication.

I hope that helps. Apologies for the LONG explanation.

Me: University Bachelor and Honours degree in Mathematics.

Xubono
Автор

In India it is taught BODMAS which stands for Bracket, Of, Division, Multiplication, Addition and Subtraction...So, basically according to that....
6÷3(1+2)
= 6÷6
=1
Next onee
is 0

youtubeviewer
Автор

A.) 6÷2 ( 1+2 )
According to BODMAS rule (Bracket of division, multiplication, addition and subtraction)
We first add 1+2 =3 (simplifying the brackets)
=6÷2(3)
Next we divide 6 and 2.
= 3(3)
=3×3
=9

B.) 9-3÷1/3+1
Again, according to BODMAS rule, we first divide.
=3÷1/3 (taken reciprocal)
=3×3
=9
Thus, 9-9+1
= 0+1
=1

Thus, final answers are 9 and 1 respectively.

Is that correct?

Also I love your videos.. Like all the puzzles and stuff are just way too cool and amazing!

queeniekaashvi
Автор

The answer for
1st Question=9
2nd Question=-1

Applied BODMAS rule . Is this the correct answer?

Cool_smiley
Автор

A) 6 ÷ 2(1+2)
6÷2(3)
3×3
Ans: 9

B) 9-3÷1/3+1
9-3×3+1
9-9+1
0+1
Ans:1

qsfviwz
Автор

As we know 1/3 can be written as 3/1 so 2nd answer is 1 and 1st one answer is 9

misanbasnet
Автор

Red: First, solve the expression inside the parentheses: 1 + 2 = 3
Then, perform the division: 6 ÷ 2 = 3
Finally, multiply the result of step 2 by the result of step 1: 3 * 3 = 9
GREEN: First, perform the division:
3
÷
1
3
=
9

1
_
3

=9
Then, subtract the result of step 1 from 9:
9

9
=
0
9−9=0
Finally, add 1 to the result of step 2:
0
+
1
=
1
0+1=1
Chat GTP answer those

kokonutkokokokokonuti
Автор

I will explain
Q1. You have to do 2+1 first getting 3 then if there is no symbol between parentheses and a num then it is multiplication so you do the rest and it equals 9
Q2. You have to do division first and that equals 9 so then left to right 9-9 equals 0 + 1 equaling 1
Answers:
Q1: 9
Q2: 1

MTGhoops
Автор

NO Dammit! In PEMDAS, 'M' comes before 'D' while in BIDMAS/BODMAS, 'D' comes before 'M'...so the first answer could be 9 or 1!! They're not the same! This is a REAL ISSUE!!

howtokdj
Автор

They are 9 and 1 (BEDMAS)
B rackets
E xponents
D division
M ultiplication
A edition
S infraction
Or
Bemdas

bigmike
Автор

First one. You do parentheses first always so it’s 6/2(3). There’s multiplication and division, but they are on the same level in PEMDAS and they operate as one function. When both are present, you go left to right. So 6/2 is 3 times (3). 3(3) is 9.

Second one. No multiplication or parentheses, so we start with division and go left to right. And since it’s expressed as one third (a fraction) not
1/3 (expression), we have to do 3/(1/3)… one third goes into 3 9 times. So now its 9-9+1, so 1.

ytuser
Автор

It's so frustrating to see this many people get it wrong. So let's explain it step by step. The first question is 6÷2(1+2). According to BEDMAS/PEDMAS, we start with the brackets, (1+2), that equals 3. Then we solve the equation from left to right, 6÷2 is 3 and 3×3 is 9, so therefore the answer for the first question is 9. 6÷2(1+2)= 6÷2×3 = 3×3 = 9. The second question is 9-3÷1/3+1. Following the rules of BEDMAS/PEDMAS, we first divde 3 by 1/3 which gives us 9, then we solve the equation from left to right, 9-9 = 0, and 0+1 is 1, so the answer to the second question is 1. 9-3÷1/3+1= 9-9+1= 0+1= 1. Thank you for coming to my ted talk.

elori
Автор

Well I get answer
1. 1
2. 1
6÷2{1+2}
6÷{2+4) The 2 outside the ()is multiplied by each individual # inside ().
6÷6 You + inside the () b/c we all know you do what's inside () 1st
1 is final answer to 6÷6

9-3÷1/3+1
9-3/1÷1/3+1 I will say where I feel everyone gets confused is with the ÷ of a fraction. All you do @ this point is make BOTH #'s fractions 1st. A whole number you always take & put a 1 underneath so 3 becomes 3/1.
9-3/1×3/1+1 In order to ÷ fractions you take the 1ST fraction & multiply it by the reciprocal of the 2ND one.
9-9/1+1 Since we know any fraction whose denominator is 1 tells us that the numerator becomes the # we use. In this case it's 9.
9-9+1
0+1
1

brandyolivarez